Biosafety of salmonella in raw vegetables. - Nillian, Elexson (2011)
Foodborne infectious diseases have emerged as an important public health problem in many countries in the last decade. The global appearance of enteric pathogens such as Salmonella which is similar foodborne diseases may challenge many countries at once. The main objective of this study is to determine the level of contamination by Salmonella spp, Salmonella Enteritidis and Salmonella Typhimurium in raw vegetables. Most Probable Number (MPN) and Multiplex Polymerase chain reaction (MPCR) have been applied as combination method to enumerate the density of Salmonella presence in the food samples and to rapidly detect multiple microorganisms in a single reaction. The MPN method is capable to measure only live and active organism. This technique results in more uniform recovery of a microbial population and the detection of the organism. Three specific primers pairs were use is ST11 and ST15, Fli15 and Typ04, Sef A-1 and Sef A-2 acts as a detection tool to genus level. The result showed that the primers amplified at 429 bp, 620 bp and 330 bp fragment respectively. This multiplex PCR represents a major of advance in terms of speed, sensitivity and specificity of diagnostic tools. A total of hundred fifty samples (n=150) were collected randomly from hypermarket and wet market in Serdang, Selangor including cabbage lettuce, cucumber and carrot which is twenty five samples (n=25) per each type. Salmonella spp was detected is 40.67%, Salmonella Enteritidis and Salmonella Typhimurium is 16.67% and 10.67% respectively in all the samples. Lettuce shows the highest contamination by Salmonella Enteritids (40%) and Salmonella Typhimurium (28%). However, 40% of Salmonella spp was detected in vegetarian burger. The density of cell concentration of Salmonella detected in all the samples were in the ranged <3 to>53 MPN/g. Most of the samples w ere in the minimum ranged of < 3 MPN/g. The survival of Salmonella Enteritidis studies in this research was tested in egg sandwiches with different temperatures and initial microbial loads with 10^1 CFU/ml and 10^3 CFU/ml. Room temperature and 4 °C were selected to determine the growth of Salmonella in different interval of incubation time from 0 hour to six hours. The initial microbial load with 10^ 3 and 10^ 1 CFU/ml was loaded in raw vegetables namely are cucumber and lettuce after there are washed with distilled water. It was found that there are slow kinetics growths of Salmonella Enteritidis in the survival of Salmonella Enteritidis in egg sandwiches. Salmonella is able to grow even at temperature of 4 °C. Microbial although was loaded in small amount for the initial stage. Initial microbial load 101 CFU/ml show the growth of Salmonella is slow and their rapidly grow in room temperature with 101 to 103 CFU/ml. The highest growth of Salmonella is from 103 CFU/ml to 104 CFU/ml within 6 hr incubation in both temperature and initial microbial load.